2020
DOI: 10.1111/nyas.14424
|View full text |Cite
|
Sign up to set email alerts
|

New developments in esophageal function testing and esophageal manifestations of connective tissue disorders

Abstract: This work summarizes new and emerging metrics and tools in esophageal function testing and their potential clinical impact. Because the diagnostic sensitivity and reliability of conventional impedance‐pH variables are suboptimal, several novel impedance parameters, such as the postreflux swallow–induced peristaltic wave index and the mean nocturnal baseline impedance, as well as mucosal impedance, are entering a validation stage prior to general clinical use. The accurate diagnosis of behavioral disorders in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Multiple mechanisms can be implicated, including xerostomia, neuropathy, cricoarytenoid joint arthritis, esophageal dysmotility, and gastroesophageal reflux [ 44 ]. Xerostomia, by interfering with the triggering of peristalsis, could result in delayed swallowing during the oral and pharyngoesophageal phases, decreased acid clearance in the esophagus, and increased symptoms of esophageal dysmotility [ 45 ]. Dysphagia may result from complications associated with xerostomia, such as opportunistic infections (Candida albicans), dental caries, and loss of teeth [ 41 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple mechanisms can be implicated, including xerostomia, neuropathy, cricoarytenoid joint arthritis, esophageal dysmotility, and gastroesophageal reflux [ 44 ]. Xerostomia, by interfering with the triggering of peristalsis, could result in delayed swallowing during the oral and pharyngoesophageal phases, decreased acid clearance in the esophagus, and increased symptoms of esophageal dysmotility [ 45 ]. Dysphagia may result from complications associated with xerostomia, such as opportunistic infections (Candida albicans), dental caries, and loss of teeth [ 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…CT: computed tomography, MRI: magnetic resonance imaging, EGD: esophagogastroduodenoscopy References:[1,[45][46][47][48][49] …”
mentioning
confidence: 99%
“…A case‐control study showed that smooth‐muscle atrophy was found in 94% of patients with SSc compared with 5% of control subjects 3 . In addition, it is known that esophageal involvements at various frequencies are found in patients with other autoimmune connective tissue diseases (CTDs) 4,5 . Thus, the presence of CTDs should be examined, if an esophageal localized muscular defect is found.…”
mentioning
confidence: 99%